Determination of thermal comfort zone for early-stage broilers - Cândido,Márcia G. L. (2016)
ABSTRACT Environmental temperatures currently considered within comfort zone for broiler rearing may be misleading or even obsolete from actual values. Some factors such as animal genetics, nutrition and poultry management, mainly acclimatization to tropical and subtropical conditions, influence in determining the comfort zone for birds. This study aimed to evaluate the effects of five different thermal environments on animal welfare and rearing performance of broiler chickens, setting an ideal temperature range (comfort zone) for each of the first three weeks of poultry breeding. The chicks (375) were randomly placed into five climatic chambers set to distinct thermal conditions, being: one as recommended by the literature, another as stated by Cassuce and the other three at different levels of apparent cold stress (mild, moderate and severe). The findings showed that best poultry performance and ideal comfort indices (based on Black Globe Humidity and Temperature Index) were achieved within a temperature range between mild cold and Cassuce comfort temperature, rather than those previously reported in the literature.